CgpCaVEManWrapper: Simple Execution of CaVEMan in Order to Detect Somatic Single Nucleotide Variants in NGS Data. Issue 1 (8th December 2016) - Jones, David; Raine, Keiran M.; Davies, Helen; Tarpey, Patrick S.; Butler, Adam P.; Teague, Jon W.; Nik‐Zainal, Serena; Campbell, Peter J.
Abstract: CaVEMan is an expectation maximization–based somatic substitution‐detection algorithm that is written in C. The algorithm analyzes sequence data from a test sample, such as a tumor relative to a reference normal sample from the same patient and the reference genome. It performs a comparative analysis of the tumor and normal sample to derive a probabilistic estimate for putative somatic substitutions. When combined with a set of validated post‐hoc filters, CaVEMan generates a set of somatic substitution calls with high recall and positive predictive value. Here we provide instructions for using a wrapper script called cgpCaVEManWrapper, which runs the CaVEMan algorithm and additional downstream post‐hoc filters. We describe both a simple one‐shot run of cgpCaVEManWrapper and a more in‐depth implementation suited to large‐scale compute farms. © 2016 by John Wiley & Sons, Inc.